2018
DOI: 10.1097/mjt.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Fractional Exhaled Nitric Oxide Levels and Efficacy of Inhaled Corticosteroids in Children With Bronchial Asthma

Abstract: To investigate correlation between fractional exhaled nitric oxide (FeNO) levels and efficacy of inhaled corticosteroids in children with bronchial asthma. Between October 2013 and December 2014, 133 cases of children with bronchial asthma were randomly divided into the glucocorticoid group (n = 67; inhaled with Seretide/Pulmicort) and the nonglucocorticoid group (n = 66; inhaled with short-acting β2 receptor agonist if needed); and alternatively 72 cases of healthy children were regarded as the control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This may be attributed to the reduced expression of inflammatory biomarkers when using ICS. 21,22 Shi et al 42 confirmed that FeNO was negatively associated with FEV 1 %pred in COPD and ACO. However, Liu et al 43…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This may be attributed to the reduced expression of inflammatory biomarkers when using ICS. 21,22 Shi et al 42 confirmed that FeNO was negatively associated with FEV 1 %pred in COPD and ACO. However, Liu et al 43…”
Section: Discussionmentioning
confidence: 93%
“…However, all of them are affected by factors such as therapeutic drugs and smoking. [21][22][23][24] Therefore, the present study was conducted to further evaluate the accuracy of FeNO, EOS, and NLR in ACO diagnosis after excluding the influence of ICS and smoking use. Congruent with some previous studies, [15][16][17][18][19][20] our results confirmed the higher levels of FeNO and EOS in ACO patients than in COPD patients, especially in those without ICS use or with a smoking history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchial asthma in children is a chronic inflammatory disease characterized by bronchial hyper-responsiveness and mediated by various cells, including mast cells, T lymphocytes and eosinophilic granulocytes (1). The main clinical symptoms included chest distress, annihilation and coughing caused by airway constriction, which can easily induce weakness of breathing, cyanosis and depression signs (2).…”
Section: Introductionmentioning
confidence: 99%